TAHARAH IN AL-JAILANI’S INTERPRETATION (STUDY OF SUFISTIC INTERPRETATION FROM HANS-GEORG GADAMER'S HERMENEUTIC PERSPECTIVE) - Hami, Widodo (PERADA, 2023)
Abstract This paper aims to demonstrate al-Jailani's interpretation of the taharah verses which differ a lot from other interpreters. According to the author, many of the taharah verses understand it from the perspective of history and fiqh, in this study it will be understood by revealing the hidden meaning behind the verse. So that taharah in the spiritual domain can be implemented and can be interpreted widely, not only in fiqh and history but also in the perspective of spirituality. According to Sufi scholars, the Koran is not only understood with a historical approach. Because they believe that the Qur'an has an outer meaning (exoteric) and an inner meaning (esoteric). Through the 'irfani (illuminative) approach, they try to uncover the deepest meaning behind the Qur'an. This research is based on library research with the object being studied are the t}aharah verses in al-Jailani's interpretation using a hermeneutic approach. The concept of taharah according to al-Jailani is not only interpreted by cleaning hadas (rutial impurity) and najis (unclean) an sich. wider than that, taharah includes cleaning the heart and adorning it with noble character, so that a pious person can reach a high degree (fana') in the sight of Allah SWT. The concept of taharah presented by al-Jailani cannot be separated from the concepts of takhal, tahalli and tajalli. A student/salik can achieve this degree with the guidance of a murshid. Kata kunci: Taharah; Sufi Interpretation; Hermeneutic